Decompressive craniectomy for malignant middle cerebral artery territory infarct: an institutional experience - Kumar, Ranjit; Tiwari, Brijesh Kumar; Pandey, Sanjeev Kumar (International Surgery Journal, 2020)
Background: Decompressive craniectomy is the surgical procedure to reduce intracranial pressure, refractory to medical measures. We have described our experience associated with the clinical profile, radiological profile, postoperative status and long term outcome in patients with malignant middle cerebral artery (MCA) territory infarct. Methods: Data were collected from patients who underwent hemispheric decompressive craniectomy for malignant MCA territory infarct in our hospital from May 2014 to June 2019. Clinical, radiological, surgical profile and long term outcome were studied. Results: There were a total of 51 patients aged between 28 years to 76 years. Hypertension (70%) was the most common comorbidity associated. All the patients had at least one focal neurological deficit at the time of presentation. Mean time from the first symptoms to surgery was 2.4 days (about 58 hours). 7 patients died within one month of the surgery. Two third improved objectively within 1 month of surgery. Out of 44 patients, who survived beyond one month, none of the patients were functionally independent after one year of surgery (modified Rankin scale (mRS) of 0 or 1). The patients had a mean mRS of 3.8 at one year. Conclusions: Over several decades decompressive craniectomy has been found to be the most effective measure to reduce mortality and morbidity associated with malignant MCA territory infarct. Early surgery (<48 hours) in patients with good Glasgow Coma scale score reduces the mortality. Larger multicentric trials are required to look at the long term effect on morbidity and mortality.